Electrochemical study of the Pt and Pt-Ni upon multiwalled carbon nanotubes - Mohammed, N.M. (American Institute of Physics Inc., 2016)
Direct methanol fuel cells have attracted great interest in the recent development of portable devices. New routes are being developed for synthesizing the catalysts used in the methanol oxidation. In this work, the electrochemical behavior of the Pt and Pt-Ni upon multiwalled carbon nanotubes, synthesized via a new modified route, has been studied. The results showed that Pt-Ni 10 has the comparable current density to the Pt 20-loading which is nearly 3 times greater than 10 Pt loading. The transfer of the polarization curve of Pt-Ni 10 towards lower polarization region following the catalyst with 20 Pt loading indicates the higher activity of the nano-electro-catalysts in the alkaline media. Also the long term efficiency and activity of the Pt-Ni with 10 loading is nearly reaching the 20 Pt-loading which is almost 10 folds greater than the 10 Pt loading. The study revealed that Ni in Pt-based nanoalloy impart not only an enhanced activity but also better durability of catalyst in direct methanol fuel cell applications. Â© 2016 Author(s).